2007
DOI: 10.1007/s00454-006-1299-y
|View full text |Cite
|
Sign up to set email alerts
|

Volume and Lattice Points of Reflexive Simplices

Abstract: Using new number-theoretic bounds on the denominators of unit fractions summing up to one, we show that in any dimension d ≥ 4 there is only one d-dimensional reflexive simplex having maximal volume. Moreover, only these reflexive simplices can admit an edge that has the maximal number of lattice points possible for an edge of a reflexive simplex. In general, these simplices are also expected to contain the largest number of lattice points even among all lattice polytopes with only one interior lattice point. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 26 publications
(30 reference statements)
0
46
0
Order By: Relevance
“…There is precisely one reflexive three-polytope with an edge of length 12, and precisely one reflexive four-polytope with an edge of length 84 (cf. [12]). …”
Section: Small Dmentioning
confidence: 99%
“…There is precisely one reflexive three-polytope with an edge of length 12, and precisely one reflexive four-polytope with an edge of length 84 (cf. [12]). …”
Section: Small Dmentioning
confidence: 99%
“…This initiated an intense study of the geometric and combinatorial properties of reflexive polytopes [14,19,31,32,40,42]. Definition 2.1.…”
Section: Reflexive Polytopesmentioning
confidence: 99%
“…Much more is known about simplicial reflexive polytopes (corresponding to Q-factorial Gorenstein toric Fano varieties). Their combinatorics is quite restrictive: The vertex-edge-graph has diameter two, and given any vertex v 2 V(P ) there exist at most three other vertices of P not contained in a facet containing v [40]. Casagrande [14] showed that the maximal number of vertices is 3n if n is even, or 3n 1 if n is odd.…”
Section: Reflexive Polytopesmentioning
confidence: 99%
“…6 Nill has constructed a sequence of reflexive simplices Q j such that dim Q j = j and the normalized volume vol Q j = h * 0 (Q j ) + · · · + h * j (Q j ) grows doubly exponentially with j [17]. Therefore, there exists a reflexive simplex Q such that h * i (Q) ≥ n for some i, and dim(Q) = O(log log n).…”
Section: Braun's Formula Let Q and Q Be Reflexive Polytopes Thenmentioning
confidence: 99%